Control adjustments in speaking: Electrophysiology of the Gratton effect in picture naming. (July 2017) - Shitova, Natalia; Roelofs, Ardi; Schriefers, Herbert; Bastiaansen, Marcel; Schoffelen, Jan-Mathijs
Abstract: Accumulating evidence suggests that spoken word production requires different amounts of top-down control depending on the prevailing circumstances. For example, during Stroop-like tasks, the interference in response time (RT) is typically larger following congruent trials than following incongruent trials. This effect is called the Gratton effect, and has been taken to reflect top-down control adjustments based on the previous trial type. Such control adjustments have been studied extensively in Stroop and Eriksen flanker tasks (mostly using manual responses), but not in the picture–word interference (PWI) task, which is a workhorse of language production research. In one of the few studies of the Gratton effect in PWI, Van Maanen and Van Rijn (2010) examined the effect in picture naming RTs during dual-task performance. Based on PWI effect differences between dual-task conditions, they argued that the functional locus of the PWI effect differs between post-congruent trials (i.e., locus in perceptual and conceptual encoding) and post-incongruent trials (i.e., locus in word planning). However, the dual-task procedure may have contaminated the results. We therefore performed an electroencephalography (EEG) study on the Gratton effect in a regular PWI task. We observed a PWI effect in the RTs, in the N400 component of the event-related brain potentials, and in the midfrontal theta power, regardless of the previous trial type. Moreover, the RTs, N400, and theta power reflected the Gratton effect. These results provide evidence that the PWI effect arises at the word planning stage following both congruent and incongruent trials, while the amount of top-down control changes depending on the previous trial type.